A REPRESENTATION OF CHARACTER EDUCATION VALUES THROUGH FIGURATIVE LIVES OF THE GEISHAS IN SNOW COUNTRY: A NEW HISTORICISM PERSPECTIVE - Lalu Muhaimi; Lalu Nurtaat; Sribagus Sribagus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2020)
Abstract: Snow Country is the story about the figurative lives of geishas in Japanese society. As a Nobel Prize recipient Snow Country is widely considered to be a masterpiece, a powerful tale of wasted love set amid the desolate beauty of western Japan, from which the writer configure and represent various cultural and educational values within Japanese community. These values are expressed through a beautiful narration of the life of three important figures, Shimamura the guest and Komako the country geisha, and another country geisha names Yoko. Shimamura somehow likes Komako and therefore visits the resort a few times. Komako really likes Shimamura that she has done a lot of things like a crazy person in love. In addition, there is a bit of healthy competition going on between Komako and Yoko which symbolizes the practices of ‘competitive’ life surrounding the Japanese. Here, as a part of cultural and educational value, the life of ‘modern’ geisha has been justified as one of the ways to keep and sustain Japanese old tradition which have become the basis of most educational practices in the country which worth following.Keywords: Character education value, figurative life, geisha, new historicism